The Epidermal Growth Factor Homology Domain of the LDL Receptor Drives Lipoprotein Release through an Allosteric Mechanism Involving H190, H562, and H586 - Zhao, Zhenze (American Society for Biochemistry and Molecular Biology, 2008)
The low density lipoprotein (LDL) receptor (LDLR) mediates efficient endocytosis of VLDL, VLDL remnants, and LDL. As part of the endocytic process, the LDLR releases lipoproteins in endosomes. The release process correlates with an acid-dependent conformational change in the receptor from an extended, “open” state to a compact, “closed” state. The closed state has an intramolecular contact involving H190, H562, and H586. The current model for lipoprotein release holds that protonation of these histidines drives the conformational change that is associated with release. We tested the roles of H190, H562, and H586 on LDLR conformation and on lipoprotein binding, uptake, and release using variants in which the three histidines were replaced with alanine (AAA variant) or in which the histidines were replaced with charged residues that can form ionic contacts at neutral pH (DRK variant). Contrary to expectation, both the AAA and the DRK variants exhibited normal acid-dependent transitions from open to closed conformations. Despite this similarity, both the AAA and DRK mutations modulated lipoprotein release, indicating that H190, H562, and H586 act subsequent to the conformational transition. These observations also suggest that the intramolecular contact does not drive release through a competitive mechanism. In support of this possibility, mutagenesis experiments showed that β-VLDL binding was inhibited by mutations at D203 and E208, which are exposed in the closed conformation of the LDLR. We propose that H190, H562, and H586 are part of an allosteric mechanism that drives lipoprotein release.